Analysis Of The Potential Content Of Micronutrients In Traditional Foods In West Pasaman District - Putri, Tika Nuansa; Kasmita, Kasmita; Yuliana, Yuliana; Gusnita, Wiwik; Santi, Titen Darlis (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research aims to analyze the potential micronutrient content in traditional foods in West Pasaman Regency as an effort to prevent stunting in children. The research method involves collecting traditional foods commonly consumed by local communities and analyzing them to identify the content of micronutrients such as vitamins, minerals and other important nutrients. The research results show that traditional foods that are widely consumed in West Pasaman Regency have great potential in providing essential micronutrients for children's growth. A number of traditional foods are high in vitamins A, D, E and K as well as minerals such as iron and zinc, which are important for healthy growth and development. Analysis of traditional foods also revealed the presence of antioxidant compounds that help protect the body from cell damage and can play a role in preventing stunting in children. These findings highlight the important role of traditional foods in providing the micronutrients needed to prevent stunting. The implications can support the promotion and increase in consumption of local, nutrient-rich foods in West Pasaman Regency as part of a strategy to prevent stunting in children.